2021
DOI: 10.1186/s12974-021-02089-z
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin 3 protects against anesthesia/surgery-induced cognitive decline in aged mice by suppressing hippocampal neuroinflammation

Abstract: Background Postoperative cognitive dysfunction (POCD) is a very common complication that might increase the morbidity and mortality of elderly patients after surgery. However, the mechanism of POCD remains largely unknown. The NAD-dependent deacetylase protein Sirtuin 3 (SIRT3) is located in the mitochondria and regulates mitochondrial function. SIRT3 is the only sirtuin that specifically plays a role in extending lifespan in humans and is associated with neurodegenerative diseases. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 66 publications
6
107
0
Order By: Relevance
“…Neuroinflammation is primarily involved in the pathological mechanism of PND ( Liu et al, 2021 ). In the present study, we measured the expression levels of TNF-α and IL-1β in the hippocampus of aged mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroinflammation is primarily involved in the pathological mechanism of PND ( Liu et al, 2021 ). In the present study, we measured the expression levels of TNF-α and IL-1β in the hippocampus of aged mice.…”
Section: Resultsmentioning
confidence: 99%
“…Various mechanisms are involved in the pathogenesis of PND, such as neuroinflammation, oxidative stress and neurodegeneration. The pathophysiological changes caused by neuroinflammation of the central nervous system are the main mechanism of PND ( Granger and Barnett, 2021 ; Liu et al, 2021 ). In the present study, we found that the expression of TNF-α and IL-1β in the hippocampus increased significantly in the PND group compared with the CON group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was also reported that Sirt3 protects against anesthesia/surgery-induced cognitive decline by suppressing hippocampal neuroinflammation. In aged mice with postoperative cognitive dysfunction, microglial activation and elevated proinflammatory cytokine levels were found to be associated with decreased SOD and Sirt3 expression in the hippocampus ( Liu et al, 2021 ). In addition, Sirt3 promoted microglial migration to the site of the lesion by upregulating the fractalkine receptor CX3CR1 in mice with ischemic stroke ( Cao et al, 2019 ).…”
Section: Role Of Sirtuins In Neuroinflammationmentioning
confidence: 99%
“…Golgi-Cox impregnation was one of the effective methods to study the morphology of neurons and visualize synaptic structural plasticity [31]. The FD Rapid GolgiStain™ Kit (FD Neurotechnologies, PK401, Columbia) was employed according to the manufacturer's instructions.…”
Section: Golgi-cox Staining and Dendritic Spine Countingmentioning
confidence: 99%